Reimagining the Margin: Space of Difference through a Visual Narrative - Haque, Abu (Imaginations)

(untitled) (York University, 2023)
Representations of space do not fittingly reflect the lived experiences of the margin. Representational spaces, on the other hand, are linked to underground social life and art (Lefebvre 39), which are expressed through complex signs and symbols, sometimes coded and sometimes not. Revisiting these spaces provides an understanding of the spatial practices of the marginalized bodies within the existing social relations. This paper interrogates the discursive practices of those mediated bodies through a visual narrative. The paper also challenges the center-periphery rhetoric, revealing an ambiguous and ambivalent marginality that is not fixed. The images are used as a methodological tool to elaborate the actions of the bodies in space. A series of exclusions intertwined within the spatial practices not only confirms the ambiguity of the margin but also reveals that it is a process of becoming.